DAKWAH DALAM MEMBINA MASYARAKAT PESISIR KELURAHAN TALAKA KECAMATAN MA’RANG KABUPATEN PANGKEP - Isma, Nur Azatil; Muhtadin (ISTIQRA: Jurnal Hasil Penelitian, 2022)
This research aims to find out and explain how da'wah develops coastal communities in Leppangeng, Talaka Village, Ma'rang District, and Pangkep Regency. This research uses a qualitative method using a phenomenological approach, while data collection in this research uses observation, in-depth interviews, and documentation, from the data that has been collected is then analyzed to produce conclusions and the conclusions in this research show that the need for da'wah in developing coastal communities in Leppangeng This can be done through lectures, discussions, outreach and empowerment which can be applied in several fields. The inhibiting factor in the process of developing da'wah is the community itself, which is still steeped in customs, so missionaries in carrying out guidance must erode these things little by little